Corporate tax competition and coordination in the European Union : what do we know ? where do we stand ? - Nicodeme, Gaetan; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
This paper reviews the rationales and facts about corporate tax coordination in Europe. Although statutory tax rates have dramatically declined, revenues collected from corporate taxation are fairly stable and there is so far no evidence of a race-to-the-bottom. The ambiguous results from economic tax theory and the institutional setting have constrained strong EU policy action in the area of tax competition. Yet, there are welfare gains to be expected from tax coordination. Following its 2001 Communication, the European Commission is currently working with Member States on the definition of a common consolidated corporate tax base for European Companies.
Economic Papers